Effect of conservation agriculture on soil organic carbon dynamics and mineral nitrogen under different fertilizer management practices in maize (Zea mays)-wheat (Triticum aestivum) cropping system - TIGGA, PRITI; MEENA, MAHESH C; DEY, ABIR; DWIVEDI, B S; DATTA, S P; JAT, H S; JAT, M L (The Indian Journal of Agricultural Sciences, 2020)
Soil organic carbon (SOC) is the center of all physical, chemical and biological properties of soils, its maintenance and buildup in soils is necessary to sustain the intensive cereal-based cropping system of Indo Gangetic plains. Intensive tillage, residue removal and indiscriminate use of fertilizers led to a continuous deterioration of soil health in Indo Gangetic parts of the country. Under this context, a field experiment on conservation agriculture (CA) was conducted at Taroari, Karnal, comprising four combinations of tillage and residue management [i.e. conventional tillage (CT) with complete residue removal (CT-RR), CT with 20% residue incorporation of wheat, 50% residue incorporation of maize and incorporation of green gram residue (CT+RI+GI), permanent beds (PB) with 20% residue retention of wheat and 50% residue retention of maize (PB+RR), and PB with 20% residue retention of wheat, 50% residue retention of maize and retention of green gram residue (PB+RR+GR)] and three nutrient management options [viz. farmers fertilization practice (FFP), recommended fertilizer dose (RDF) and site-specific nutrient management (SSNM)]. The results showed that, there was an increase in SOC mainly the active SOC pools, permanganate oxidizable-C (1.70 g/kg), hot water extractable-C (0.32 g/kg) and soil microbial biomass C (310 mg/kg) under CA-based treatment (PB+RR+GR) compared to CT (0.58, 0.23 g/kg, 183 mg/kg, respectively). Also, the mineral N was invariably greater under residue treatments. Therefore, crops residue retention as well as balanced fertilization (RDF and SSNM) under CA helped in improving SOC; mineral N and soil aggregation stability which can lead to increased sustainability under cereal-based intensive cropping systems.